Handbook for Preparing a Resettlement Action Plan - International Finance Corporation (Washington, DC, 2013)
This handbook intends to document the essential steps for best practice in the design, and implementation of resettlement action plans. Given that involuntary resettlement entails both the physical displacement of peoples, and the disruption of their livelihoods, social development specialists at the International Finance Corporation (IFC), worked together with project developers to ensure consistent, and pragmatic application of the Bank Group policies, and guidelines, contributing to the mitigation of environmental, and social risks. The handbook outlines the policy, and principles of resettlement, stipulating these principles as follows: 1) involuntary resettlement should be avoided; 2) where involuntary resettlement is unavoidable, affected people should be compensated fully, and fairly for lost assets; 3) involuntary resettlement should be conceived as an opportunity to improve the livelihoods of the affected people, and, undertaken accordingly; and, 4) people affected by involuntary resettlement, should be consulted, and involved in resettlement planning, to ensure that mitigation, and benefits are appropriate and sustainable. Section I presents the scope of application, reviewing the types of resettlement, public disclosure requirements, and special considerations. Section II examines the components of a resettlement action plan, through the identification of project impacts, and affected population - mapping, census, inventory of affected assets, socioeconomic studies, and consultation processes - to the legal framework on compensation, resettlement assistance, budget and implementation schedule, in addition to grievance redress and, monitoring and evaluation. Sections III and IV present an implementation checklist, and outline a resettlement action plan, respectively.